Limiting Behavior of Center Manifolds for Stochastic Evolutionary Equations with Time Delay in Varying Phase Spaces - Ma, Hongyu (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study a class of stochastic evolutionary equations driven by colored noise with the time delay in varying phase spaces. We first prove a property of the nonlinear operator $J^ε_ρ$ and a convergence Lemma. And then, we derive the Lipschitz convergence of center manifolds in varying phase spaces.